2018
DOI: 10.1021/acs.langmuir.8b02190
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Condensation of Mucins into Nanoparticles

Abstract: Mucins are high molar mass glycoproteins that assume an extended conformation and can assemble into mucus hydrogels that protect our mucosal epithelium. In nature, the challenging task of generating a mucus layer, several hundreds of micrometers in thickness, from micrometer-sized cells is elegantly solved by the condensation of mucins inside vesicles and their on-demand release from the cells where they suddenly expand to form the extracellular mucus hydrogel. We aimed to recreate and control the process of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 46 publications
1
25
0
1
Order By: Relevance
“…These simulations demonstrated that there are no topological or steric barriers to formation of the beaded filament by full-length MUC2 ( Figure 6 J) and that compact or expanded PTS regions can both be accommodated ( Figure S8 E). The former would correspond to pre-glycosylated or calcium-bound glycosylated condensed states ( Verdugo et al, 1987 ; Yan et al., 2018 ), whereas the latter would correspond to unfurled, hydrated states. A direct comparison of the simulations with measurements on polymers of secreted mucins cannot be made because the secreted polymers lack the filament scaffold of the assembly intermediate characterized in this work.…”
Section: Resultsmentioning
confidence: 99%
“…These simulations demonstrated that there are no topological or steric barriers to formation of the beaded filament by full-length MUC2 ( Figure 6 J) and that compact or expanded PTS regions can both be accommodated ( Figure S8 E). The former would correspond to pre-glycosylated or calcium-bound glycosylated condensed states ( Verdugo et al, 1987 ; Yan et al., 2018 ), whereas the latter would correspond to unfurled, hydrated states. A direct comparison of the simulations with measurements on polymers of secreted mucins cannot be made because the secreted polymers lack the filament scaffold of the assembly intermediate characterized in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Different mechanisms have already been proposed to regulate the binding of molecules to mucin [31]. In general, the occurring mechanisms affect the fate of the particles facing and entering the mucus barrier and their mutual interaction may allow tuning the mucus gel properties, and strengthening or weakening the gel mesh [32,33].…”
Section: Resultsmentioning
confidence: 99%
“…Massa Molar (137)(138)(139) Penampilan Densitas (140)(141)(142) Titik Lebur (143)(144)(145) Titik Didih (146)(147)(148) Kelarutan (149)(150)(151) Dalam Air (152)(153)(154) 58,44 g/mol Massa [222][223][224][225][226]…”
Section: Sifat Fisika Dataunclassified